2018
DOI: 10.3390/children5010011
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on Vitamin D Deficiency and Metabolic Syndrome in Obese Children: What Does the Evidence from Saudi Arabia Tell Us?

Abstract: Obesity and vitamin D deficiency represent major health problems among Saudi children, and have been linked to chronic diseases. Obese children are at risk of developing vitamin D deficiency, which appears to have negative influences on energy homeostasis, impeded bone mineralisation, insulin resistance and inflammation. Evidence supporting the association between vitamin D deficiency of obese children and metabolic syndrome has not specifically been studied in early childhood. The mechanisms through which vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 97 publications
(125 reference statements)
4
13
0
Order By: Relevance
“…Furthermore, this study and other studies showed that there are gender differences in the prevalence of MetS, being more prevalent in men than women [22,23]. Additionally, previous studies have stated that metabolic syndrome and overweight is connected with micronutrients, such as vitamin D, or social factors, such as eating with familiars or eating with the TV on [24,25]. However, to date, no unified definition exists to assess the risk of MetS in children and adolescents.…”
Section: Introductionsupporting
confidence: 47%
“…Furthermore, this study and other studies showed that there are gender differences in the prevalence of MetS, being more prevalent in men than women [22,23]. Additionally, previous studies have stated that metabolic syndrome and overweight is connected with micronutrients, such as vitamin D, or social factors, such as eating with familiars or eating with the TV on [24,25]. However, to date, no unified definition exists to assess the risk of MetS in children and adolescents.…”
Section: Introductionsupporting
confidence: 47%
“…Although several epidemiological studies have observed that vitamin D deficiency was associated with obesity in children, the causality of association has remained uncertain 5 8 14 32–36. Low levels of 25(OH)D concentration may work as a marker rather than a cause of obesity 37.…”
Section: Discussionmentioning
confidence: 99%
“…A review of human, animal, and cellular studies showed inconsistent ndings that a low serum vitamin D level was correlated with the cause of obesity (31). The mechanisms of association between vitamin D de ciency and MetS in obese children should be elucidated in prospective studies and provide health strategies for decreasing the risk of obesity and metabolic syndrome among children and adolescents (32).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of vitamin D de ciency among children and adolescents dependents on some factors including ethnicity, sex, physical inactivity, low sun exposure, increased TV watching, low milk intake and high soft drink intake that are also play a role in increased risk of MetS (32,33). The association between low serum 25(OH) D and MetS is a concern in pediatric population because children and adolescents with MetS are at high risk of future cardiovascular disease and type II diabetes.…”
Section: Resultsmentioning
confidence: 99%